Electromechanical Regulation Underlying Protein Nanoparticle-Induced Osmotic Pressure in Neurotoxic Edema - Zheng Z; Nie A; Wu X; Chen S; Zhang L; Yang D; Shi Y; Xiong X; Guo J (International Journal of Nanomedicine)
Zihui Zheng,1,2,* Aobo Nie,1,* Xiaojie Wu,1 Shi Chen,1 Lijun Zhang,1 Dongqing Yang,3 Yuqing Shi,1 Xiyu Xiong,1 Jun Guo1,2 1Department of Biochemistry and Molecular Biology, School of Medicine, Nanjing University of Chinese Medicine, Nanjing, Jiangsu, 210023, People’s Republic of China; 2State Key Laboratory on Technologies for Chinese Medicine Pharmaceutical Process Control and Intelligent Manufacture, Nanjing University of Chinese Medicine, Nanjing, 210023, People’s Republic of China; 3Department of Public Health, School of Medicine, Nanjing University of Chinese Medicine, Nanjing, Jiangsu, 210023, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jun Guo, School of Medicine, Nanjing University of Chinese Medicine, Nanjing, Jiangsu, 210023, People’s Republic of China, Tel +86 13813909055, Email guoj@njucm.edu.cnPurpose: Osmotic imbalance is a critical driving force of cerebral edema. Protein nanoparticles (PNs) amplify intracellular osmotic effects by regulating membrane potential and homeostasis of water and multiple ions. This study has investigated how PNs control the neuronal swelling through electromechanical activity.Methods: The fluorescence resonance energy transfer (FRET)-based Vimentin force probe was used to real-time monitor the osmotic tension in neurons. Patch clamp and the living cell 3D imaging system were applied to explore the relationship between cell electromechanical activity and cell volume in different cytotoxic cell models. Cytoplasmic PN amount measured by the NanoSight instrument, ion contents detected by the freezing point osmometer and ion imaging were performed to investigate the role of PNs in regulating cell swelling.Results: We observed a close association between neuronal swelling and changes in osmotic tension and membrane potential. The tension effect of biological osmotic pressure (OP) relies on electromechanical cooperation induced by intracellular PN and Ca2+ levels. PNs increment results from cytoplasmic translocation of intracellular various proteins. Alterations in Ca2+ content are involved in the membrane potential transition between depolarization and hyperpolarization in a PN-dependent manner. Chemical signals-mediated sensitization of ion channels has an indispensable effect on PN-induced ion increments. Notably, aquaporin-mediated water influx recovers membrane potential and enhances osmotic tension controlling neuronal swelling.Conclusion: Our findings indicate that PNs, Ca2+, and water are pivotal in electromechanical cooperation and provide insights into the biological OP mechanisms underlying neurotoxic edema. Keywords: protein nanoparticle, electromechanical cooperation, osmotic tension, membrane potential, neuronal swelling